Pengaruh Teamwork terhadap Kinerja Karyawan melalui Job Satisfaction - Dini Hariani Octavia; Budiono Budiono (Jurnal Ilmu Manajemen, 2021)
This research aims to examine and analyze the effect of teamwork on employee performance through employees' job satisfaction at PT. Jasa Raharja Cabang Jawa Timur. This research is causality research with a quantitative approach. The population in this research is 159 employees. The sample was collected through a random sampling technique and obtained 62 respondents”the statistical analysis using Partial Least Square with SmartPLS 3.0. The results show that teamwork has a positive and significant influence on employee performance, teamwork has a positive and significant influence on job satisfaction. Job satisfaction has a positive and significant influence on employee performance. Teamwork has no significant influence on employee performance through job satisfaction. Companies can encourage employees to do teamwork by creating teams to complete tasks.